D-Aspartate Modulates Nociceptive-Specific Neuron Activity and Pain Threshold in Inflammatory and Neuropathic Pain Condition in Mice. (5th January 2015) - Boccella, Serena; Vacca, Valentina; Errico, Francesco; Marinelli, Sara; Squillace, Marta; Guida, Francesca; Di Maio, Anna; Vitucci, Daniela; Palazzo, Enza; De Novellis, Vito; Maione, Sabatino; Pavone, Flaminia; et al.
Abstract : D-Aspartate (D-Asp) is a free D-amino acid found in the mammalian brain with a temporal-dependent concentration based on the postnatal expression of its metabolizing enzyme D-aspartate oxidase (DDO). D-Asp acts as an agonist on NMDA receptors (NMDARs). Accordingly, high levels of D-Asp in knockout mice for Ddo gene ( Ddo −/− ) or in mice treated with D-Asp increase NMDAR-dependent processes. We have here evaluated in Ddo −/− mice the effect of high levels of free D-Asp on the long-term plastic changes along the nociceptive pathway occurring in chronic and acute pain condition. We found that Ddo −/− mice show an increased evoked activity of the nociceptive specific (NS) neurons of the dorsal horn of the spinal cord (L4–L6) and a significant decrease of mechanical and thermal thresholds, as compared to control mice. Moreover, Ddo gene deletion exacerbated the nocifensive responses in the formalin test and slightly reduced pain thresholds in neuropathic mice up to 7 days after chronic constriction injury. These findings suggest that the NMDAR agonist, D-Asp, may play a role in the regulation of NS neuron electrophysiological activity and behavioral responses in physiological and pathological pain conditions.